Introduction to particle technology - Rhodes, Martin; Seville, Jonathan (Wiley, 2024)
INTRODUCTION TO PARTICLE TECHNOLOGYA new edition of the indispensable guide to particulates and powdersParticle technology concerns the formation, processing and properties of the particles and powders which make up many of the products that surround us. Such products range from the cement and aggregate in the built environment to pharmaceuticals and processed foods. Most of the process industries involve particles, either as essential components such as catalysts or as intermediate or final products, and minerals such as the rare earths that are generally mined and processed in particulate form. Particles can have many beneficial uses but they can also cause harm in the environment and, through inhalation, to the individual.